The emergence of resilience: Recovery trajectories in sleep functioning after a major stressor. - Gucciardi, Daniel; Lang, J.W.B.; Lines, Robin; Chapman, Michael; Ducker, Kagan; Peeling, P.; Crane, M.; Ntoumanis, Nikos; Parker, Sharon; Thogersen-Ntoumani, Cecilie; Quested, Eleanor; Temby, P. (2021)
There is intuitive and practical appeal to the idea of emergent resilience, that is, sustaining healthy levels of functioning or recovering quickly after some degree of deterioration following exposure to heightened risk or vulnerability. Scholars typically utilize mean levels of functioning indices to identify qualitatively distinct latent subgroups of individuals who share similar patterns of change over time. We propose and showcase an alternative, yet complementary operationalization of emergent resilience via temporal changes in within-person variability. Twenty-nine male personnel (26.25 ± 2.67 years) from the Australian Army who passed a 3-week Special Forces Selection Course provided device-based assessments of sleep functioning for seven nights immediately following course completion. Participants also provided a hair sample for cortisol analysis prior to and immediately after the selection course as an index of accumulated stress, and self-reported their adaptability prior to the 7-day monitoring period. We combined latent growth modeling with an exponential variance function to capture fluctuations around latent means and their change over time. Consistent with our conceptualization of “bounce back” emergent resilience, within-person variability in sleep duration decreased each night by around 10%, which reflects a meaningful small mean decrease over time. We also revealed differential effects of the predictor variables; biological stress primarily influenced the total sleep duration on the first night of the 7-day monitoring period, whereas adaptability largely affected temporal changes in the within-person residual variances. These findings underscore the importance of synergizing concept, operationalization, and method for the science of human resilience. (PsycInfo Database Record (c) 2021 APA, all rights reserved)